A STUDY OF POLYPREDICATIVE UNITS WITH COMPLEX SUBJECT VERBS - D.R. Teshaboyev (Western European Studies, 2025)
This article analyzes complex polypredicative units with a subordinate clause, their emergence with various grammatical means, semantic and structural features of compound sentences that appear in different syntactic functions in relation to the first part, and at the same time, scientific views and conclusions are given on the discovery of new aspects of the complex polypredicative unit with a subordinate clause
Keywords: compound sentence; organized polypredicative unit with a subordinate clause; compound sentence without a conjunction